4D ultrafast ultrasound flow imaging: in vivo quantification of arterial volumetric flow rate in a single heartbeat. (3rd November 2016) - Correia, Mafalda; Provost, Jean; Tanter, Mickael; Pernot, Mathieu
Abstract: We present herein 4D ultrafast ultrasound flow imaging, a novel ultrasound-based volumetric imaging technique for the quantitative mapping of blood flow. Complete volumetric blood flow distribution imaging was achieved through 2D tilted plane-wave insonification, 2D multi-angle cross-beam beamforming, and 3D vector Doppler velocity components estimation by least-squares fitting. 4D ultrafast ultrasound flow imaging was performed in large volumetric fields of view at very high volume rate (>4000 volumes s −1 ) using a 1024-channel 4D ultrafast ultrasound scanner and a 2D matrix-array transducer. The precision of the technique was evaluated in vitro by using 3D velocity vector maps to estimate volumetric flow rates in a vessel phantom. Volumetric Flow rate errors of less than 5% were found when volumetric flow rates and peak velocities were respectively less than 360 ml min −1 and 100 cm s −1 . The average volumetric flow rate error increased to 18.3% when volumetric flow rates and peak velocities were up to 490 ml min −1 and 1.3 m s −1, respectively. The in vivo feasibility of the technique was shown in the carotid arteries of two healthy volunteers. The 3D blood flow velocity distribution was assessed during one cardiac cycle in a full volume and it was used to quantify volumetric flow rates (375  ±  57 ml min −1 and 275  ±  43 ml min −1 ). Finally, the formation of 3D vortices at the carotid artery bifurcation was imaged at high volume rates.